1999
DOI: 10.1021/om981032m
|View full text |Cite
|
Sign up to set email alerts
|

Reactions of AlR3 (R = Me, Et) with H2NCH2CH2NMe2:  Synthesis and Characterization of Amido- and Imidoalanes

Abstract: The reactions of R3Al (R = Me, Et) with N,N-dimethylethylenediamine (DMEDA) in a 1:1 molar ratio produce adducts, R3Al·NH2C2H4NMe2 (1a, R = Me; 1b, R = Et), which upon heating in refluxing toluene result in alkane elimination to afford the chelated monomers (2a, R = Me; 2b, R = Et), respectively. Compounds 2a,b form adducts with 1 equiv of R3Al through the 3-coordinate nitrogen atom to produce (3a, R = Me; 3b, R = Et), which can be alternatively prepared by the reaction of R3Al with DMEDA in a 2:1 molar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 55 publications
2
13
0
Order By: Relevance
“…A thorough literature search for this type of compounds was done and we found that a hexameric aluminum imide with six NMe 2 groups has been reported. [2] Treatment of 2 with SiMe 3 Br or SiMe 3 Cl in toluene under refluxing conditions resulted in the formation of compounds [BrAlNCH 2 (C 4 H 3 S)] 6 (3) and [ClAlNCH 2 (C 4 H 3 S)] 6 (4), respectively. In a similar way, PhCϵCH reacts with 2 to give [PhCϵCAlNCH 2 (C 4 H 3 S)] 6 (5) and evolution of H 2 (Scheme 1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A thorough literature search for this type of compounds was done and we found that a hexameric aluminum imide with six NMe 2 groups has been reported. [2] Treatment of 2 with SiMe 3 Br or SiMe 3 Cl in toluene under refluxing conditions resulted in the formation of compounds [BrAlNCH 2 (C 4 H 3 S)] 6 (3) and [ClAlNCH 2 (C 4 H 3 S)] 6 (4), respectively. In a similar way, PhCϵCH reacts with 2 to give [PhCϵCAlNCH 2 (C 4 H 3 S)] 6 (5) and evolution of H 2 (Scheme 1).…”
Section: Resultsmentioning
confidence: 99%
“…In our continuing efforts to synthesize functionalized aluminum imides, which can act as potential complexation agents, we have treated 2-cyanothiophene with AlH 3 ·NMe 3 . Herein we report the synthesis and metathesis reactions of an aluminum imide containing six thiophene groups, [HAlNCH 2 (C 4 H 3 S)] 6 (2).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since AlH groups are capable of hydrogen elimination reactions with NH groups, a hybrid pre-ceramic precursor for Al-Si-C-N nanocomposites has been prepared by the reaction of (HAlN i Pr) 6 with a ring-type [MeSi(H)NH] n , but no structure of the precursor molecule was reported. [3] Although many cage-type compounds containing the (AlN) 6 skeleton such as (HAl-NCH 2 R) 6 (RAlNR 0 ) 6 (R 0 = C 2 H 4 NMe 2 ) have been prepared [8,9] no cage-type molecule containing (AlN) 6 skeleton coordinated with silylamino groups has been reported to date.…”
Section: Introductionmentioning
confidence: 99%
“…Compounds containing Al-N bonds are important due primarily to their various applications as reducing agents [40], important synthetic intermediates [41,42] and as precursor for chemical vapour deposition of aluminum nitride [43]. This class of compounds containing Al-N bonds also incorporate aluminum imide clusters which are oligomeric in nature and are of the composition (RNAlH)n (n = 4, 6, or 8) [44][45][46].…”
Section: Surface Fluorination Of the Heptameric Aluminum Imide Clustersmentioning
confidence: 99%